Editorial: Clinical implementation of precision oncology data to direct individualized and immunotherapy-based treatment strategies - Young, Nicholas A.; Prosperi, Jenifer R.; Freud, Aharon G.; Yee, Nelson S.; Petricoin, Emanuel F. (Frontiers in Immunology, 2025)
Graphical AbstractGraphical summary.